2013
DOI: 10.1088/1748-0221/8/12/c12046
|View full text |Cite
|
Sign up to set email alerts
|

X-ray induced photocurrent characteristics of CVD diamond detectors with different carbon electrodes

Abstract: Diamond has unique properties which make it suitable for a broad range of radiation detection applications ranging from particle timing and spectroscopy, to neutron, UV and X-ray sensors. In X-ray dosimetry, the atomic number of diamond (Z = 6) close to that of the human tissues (Z = 7.42) allows to mimic the real absorbed dose avoiding off-line recalculations. Moreover, its low atomic number and the capability to withstand high radiation fluxes make possible its use as beam monitor without altering significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…In this experiment, the shutter of the X-ray source was alternately opened and closed for periods of 30 s with a fixed dose rate of 7 mGy/s. Similar to inorganic X-ray detectors, our devices showed linear relationships between the photocurrent and dose rate following the Fowler model [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this experiment, the shutter of the X-ray source was alternately opened and closed for periods of 30 s with a fixed dose rate of 7 mGy/s. Similar to inorganic X-ray detectors, our devices showed linear relationships between the photocurrent and dose rate following the Fowler model [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, in many cases, it is possible to improve the electrical conduction at the diamond/metal interface by inducing a graphitic layer underneath the diamond substrate surface [77]. Preferred materials for diamond dosimeters electrodes are Al [68,78,79], Cr/Au [65,67,80], Ag [81]. Amorphous carbon blended with nickel (C/Ni) electrodes for polycrystalline and monocrystalline diamonds are also used to produce near-tissue equivalent detectors [51,82].…”
Section: Diamond Contactsmentioning
confidence: 99%
“…demonstrated that diamond-like-carbon multi-layer contacts permit the fabrication of devices with a remarkable sensitivity to very low dose rates using the bias voltage as a key operative parameter for different dose rate ranges. Concerning the importance of contact shape, both circular [68,79,81] and square contacts [85] are widely used without evidence of advantages of one over the other.…”
Section: Diamond Contactsmentioning
confidence: 99%
“…A diamond photodiode was characterised under the illumination of soft X-rays (0.25 keV to 7 keV) at room temperature [36]; the electron-hole pair creation energy was reported to be 13.25 eV ± 0.5 eV. The effect of different amorphous carbon electrodes on CVD diamond detectors has been studied [37]; whilst the devices showed low leakage currents (bulk resistivity of at least 2.8 × 10 14 Ω cm at applied electric field strengths of ± 0.3 V μm -1 ), a reported drawback was the instability of the photocurrent generated from illumination of a Mo target X-ray tube, at high applied potential differences [37]. In other work, a single crystal CVD diamond detector was characterised under the illumination of 10.6 keV and 12.5 keV X-rays; a linear response as a function of photon flux was measured [38].…”
Section: Introductionmentioning
confidence: 99%